Source indicators of biomass burning associated with inorganic salts and carboxylates in dry season ambient aerosol in Chiang Mai Basin, Thailand - Ying I. Tsai (2018)
PM10aerosol was collected between February and April 2010 at an urban site (CMU) and an industrial site (TOT) in Chiang Mai, Thailand, and characteristics and provenance of water-soluble inorganic species, carboxylates, anhydrosugars and sugar alcohols were investigated with particular reference to air quality, framed as episodic or non-episodic pollution. Sulfate, a product of secondary photochemical reactions, was the major inorganic salt in PM10, comprising 25.9% and 22.3% of inorganic species at CMU and TOT, respectively. Acetate was the most abundant monocarboxylate, followed by formate. Oxalate was the dominant dicarboxylate. A high acetate/formate mass ratio indicated that primary traffic-related and biomass-burning emissions contributed to Chiang Mai aerosols during episodic and non-episodic pollution. During episodic pollution carboxylate peaks indicated sourcing from photochemical reactions and/or directly from traffic-related and biomass burning processes and concentrations of specific biomarkers of biomass burning including water-soluble potassium, glutarate, oxalate and levoglucosan dramatically increased. Levoglucosan, the dominant anhydrosugar, was highly associated with water-soluble potassium (r=0.75-0.79) and accounted for 93.4% and 93.7% of anhydrosugars at CMU and TOT, respectively, during episodic pollution. Moreover, levoglucosan during episodic pollution was 14.2-21.8times non-episodic lows, showing clearly that emissions from biomass burning are the major cause of PM10episodic pollution in Chiang Mai. Additionally, the average levoglucosan/mannosan mass ratio during episodic pollution was 14.1-14.9, higher than the 5.73-7.69 during non-episodic pollution, indicating that there was more hardwood burning during episodic pollution. Higher concentrations of glycerol and erythritol during episodic pollution further indicate that biomass burning activities released soil biota from forest and farmland soils. © 2012 Elsevier Ltd.